Brain surgery for beginners : and other major operations for minors - Parker, Steve, 1952-; West, David (Brookfield, Conn. : Millbrook Press, 1995)
Looks at all aspects of the human body from the vantage point of the brain.
Includes index.
"A scalpel-free guide to your insides"--Cover.
"First published in 1993 in Great Britain by Simon & Schuster Young books"--Verso t.p.
Booklist, May 1995.
Booklist.
5.4
Keywords: Brain -- Juvenile literature; Neurophysiology -- Juvenile literature; Brain; Brain; Brain; Neurophysiology